CaII H&K emission distribution of ∼ 120 000 F, G and K stars in LAMOST DR1. (August 2015) - Zhao, Jing-Kun; Oswalt, Terry D.; Chen, Yu-Qin; Shi, Jian-Rong; Tan, Ke-Feng; Fang, Xiang-Song; Zhao, Gang; Yang, Ming; Zhang, Yong; Hou, Yong-Hui; Wang, Yue-Fei
Abstract We present chromospheric activity index SHK measurements for 119 995 F, G and K stars with high signal-to-noise ratio (S/N > 80) spectra, extracted from LAMOST DR1 in SDSS g band. The index δS for each of these stars is calculated by the difference between its SHK value and the baseline determined from very inactive stars. The effect of metallicity on measurement of δS varies with stellar Teff. No evident Vaughan-Preston gap appears in our sample. The relation between δS and vertical distance from the Galactic plane is determined for stars with Teff < 5500 K. Stars with higher δS tend to be closer to the Galactic plane. Two open clusters in the DR1 sample, M45 and M67, exhibit the expected general trend that δS decays with age. For stars with Teff > 5500 K, similar δS levels appear in both young and old cluster stars, which supports Pace's suggestion that caution should be exercised when deriving the age of a single star by using its chromospheric activity. Finally, we investigate the relation between δS and the kinematics of our sample.